Pengaruh Gaya Kepemimpinan dan Lingkungan Kerja terhadap Kinerja Karyawan - Salsabilla Anjani Putri (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
This study aims to determine how much influence leadership style and work environment have on employee performance at Company X. In this study, the method used is quantitative with data collection through questionnaires measured with a Likert scale. The sampling technique used is saturated sampling technique, where the entire employee population is sampled in this study. Data analysis was carried out using validity and reliability tests, as well as classical assumption tests such as linearity tests, hypothesis tests, and multiple linear regression, with the help of SPSS 26 software. The results of the analysis show that the leadership style variable has a significant effect on employee performance. This is evidenced by the calculated t value of 4.753 which is greater than the t table of 1.663, indicating a partial influence of leadership style on employee performance. Likewise, the work environment variable also has a significant effect on employee performance, with a calculated t value of 3.619 which is greater than the t table of 1.663. Analysis using the F-test shows that leadership style and work environment together have a significant influence on employee performance, with a calculated F-value of 12.823, which is greater than the F-table of 3.108, and a significance value of 0.000, which is less than 0.05. Based on the results of this study, it can be concluded that leadership style and work environment have a significant influence on employee performance at Company X. Therefore, the company needs to pay attention to both factors to improve employee performance.